Avaliação da imunogenicidade e proteção induzida por uma proteína hipotética de Leishmania contra leishmaniose tegumentar. - Marcelo Moreira de Jesus (2023)
ABSTRACT Tegumentary leishmaniasis (TL) is the most common form of human leishmaniasis and manifests as cutaneous and/or mucosal lesions that can lead to morbidity and even mortality in a range of patients. According to the World Health Organization, the disease affects approximately 0.6 to 1.0 million people worldwide each year, and despite the justifiable need for investments in prevention and control, TL remains a neglected disease. Currently, there are no vaccines for TL, and drug therapies cause various undesirable side effects. Previously, it has been demonstrated that a hypothetical amastigote-specific protein of Leishmania, called LiHyp1, belonging to the superoxidoreductase family, was tested as a vaccine and protected BALB/c mice from infection by Leishmania infantum, species able to cause visceral leishmaniasis. In the present study, the efficacy of the LiHyp1 protein in a vaccine against L. amazonensis infection, a species causing TL, was evaluated. For this purpose, BALB/c mice were immunized with rLiHyp1 associated with the adjuvant saponin (rLiHyp1/S) or incorporated into micelles (rLiHyp1/M), and subsequently, immunological and parasitological responses were evaluated before and/or after infection. Results demonstrated that both rLiHyp1/S and rLiHyp1/M induced a polarization of the immune response towards Th1 type, characterized by significantly increased production of IFN-γ, IL-2, TNF-α, and IL-12, nitrite, and IgG2a isotype antibodies, as compared to saline, saponin and micelle groups. Additionally, vaccinated groups showed low concentrations of IL-4 and IL-10, as well as IgG1 antibodies, both before and after challenge. It was also observed that the main cells responsible for IFN-γ production were subtype T CD4+ and CD8+ cells. Finally, immunized mice showed significant reductions in the parasite load in infected tissue, as well as in some of the internal organs, demonstrating the protective capacity of the vaccines. In conclusion, data suggest that rLiHyp1 associated with saponin or in micelles could be considered as a vaccine candidate against TL.